User Well-Being in Kitchen Environment Design from a Positive Psychology Perspective: A Quantitative and Qualitative Literature Analysis - Qi Song; Min Huang; Zhipeng Ren; Xiayan Lin; Shimin Li; Bingjie Sun; Yuting Li (Buildings)
This paper systematically discusses the impact of kitchen environment design on users’ well-being. Based on the user-centered design concept, this paper focuses on the theoretical framework of positive psychology and combines quantitative and qualitative research methods. Firstly, using bibliometric analysis tools (CiteSpace 6.1.R1 and VOSviewer 1.6.20), 1256 related articles in the Web of Science Core database were analyzed to reveal the multidimensional association between kitchen design and user well-being. It was found that improving kitchen air quality, optimizing space layout design, intelligent design, and family interaction significantly improve users’ mental health and happiness. Then, based on the PERMA model of positive psychology, this paper discusses the support path of kitchen design to users’ psychological needs from five dimensions: positive emotion, engagement, relationships, meaning, and accomplishment. Optimizing the kitchen environment can enhance user experience by creating an immersive experience and positive feedback and promoting family communication, social interaction, cultural heritage, and sustainable development. Based on research results and cutting-edge design cases in the discussion section, a home kitchen design strategy for improving user welfare through the PERMA model is proposed. Finally, follow-up research can further explore the differentiated needs of different cultural backgrounds and user groups to promote the combined application of innovative kitchen technology and positive psychology and further focus on kitchen environment and health equity, especially for developing and vulnerable countries—group-specific needs.